Information maintenance of aircraft’s automatic control using GNSS system - Ковалевський, Е. О.; Кондратюк, В. М. (Proceedings of National Aviation University (archive), 2013)
The variant of information maintenance of aircraft’s automatic control using satellite navigation system for providing landing approach and landing has been considered in this research. Calculation ratios for definition of coarse deviations have been given. Error statistics of determination of deviations have been investigated